2006
DOI: 10.1158/0008-5472.can-06-1457
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tissue Transglutaminase Leads to Constitutive Activation of Nuclear Factor-κB in Cancer Cells: Delineation of a Novel Pathway

Abstract: The transcription factor nuclear factor-KB (NF-KB) plays an important role in regulating cell growth, apoptosis, and metastatic functions. Constitutive activation of NF-KB has been observed in various cancers; however, molecular mechanisms resulting in such activation remain elusive. Based on our previous results showing that drug-resistant and metastatic cancer cells have high levels of tissue transglutaminase (TG2) expression and that this expression can confer chemoresistance to certain types of cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
213
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(224 citation statements)
references
References 41 publications
11
213
0
Order By: Relevance
“…On the contrary, in WT, the increased expression of TG2 induced by LPS might cause a continuous activation cycle in the inflammation process. Similarly, it has been reported that overexpression of TG2 in cancer cells induces constitutive activation of NF-B (44).…”
Section: Discussionmentioning
confidence: 65%
“…On the contrary, in WT, the increased expression of TG2 induced by LPS might cause a continuous activation cycle in the inflammation process. Similarly, it has been reported that overexpression of TG2 in cancer cells induces constitutive activation of NF-B (44).…”
Section: Discussionmentioning
confidence: 65%
“…NF-kappa B (NF-κB) or Rel proteins comprise a family of Protein Cell & tence of NF-κB in the nucleus, is shown in a wide variety of tumor types, such as lymphoma, liver cancer, lung cancer, breast cancer, etc (Mann et al, 2006;Qiao et al, 2006;Baby et al, 2007;Lenz et al, 2008). Besides, NF-κB is activated in response to tobacco, stress, dietary agents, obesity, alcohol, infectious agents, irradiation, and environmental stimuli that commonly contribute to carcinogenesis.…”
Section: Nf-κb Signaling Transduction Pathwaymentioning
confidence: 99%
“…By using specific silencing or overexpression of TAK1 targets, we demonstrate that the main TG2 regulator in the non-canonical pathway is the NF-kB complex. As TG2 is a known inducer of NF-KB activity in OC (Cao et al, 2008) and in other cancer cells (Mann et al, 2006), it appears that a forward positive feed loop exists between the enzyme and NF-kB.…”
Section: Tissue Transglutaminase L Cao Et Almentioning
confidence: 99%
“…Tissue transglutaminase (TG2), an enzyme overexpressed in epithelial malignancies (Mann et al, 2006;Satpathy et al, 2007), participates in Ca þ þ -dependent protein post-translational modifications and cross-linking by transferring acyl groups between glutamine and lysine residues (Pincus and Waelsch, 1968). We reported that TG2 is upregulated in ovarian tumors Satpathy et al, 2007) and has a critical role in the process of epithelial-to-mesenchymal transition (EMT), a hallmark of cancer progression.…”
Section: Introductionmentioning
confidence: 99%